2001
DOI: 10.1161/hq0801.095151
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplements Block the Response of HDL to Simvastatin-Niacin Therapy in Patients With Coronary Artery Disease and Low HDL

Abstract: Abstract-One strategy for treating coronary artery disease (CAD) patients with low HDL cholesterol (HDL-C) is to maximally increase the HDL-C to LDL-C ratio by combining lifestyle changes with niacin (N) plus a statin. Because HDL can prevent LDL oxidation, the low-HDL state also may benefit clinically from supplemental antioxidants. Lipoprotein changes over 12 months were studied in 153 CAD subjects with low HDL-C randomized to take simvastatin and niacin (S-N), antioxidants (vitamins E and C, ␤-carotene, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 54 publications
5
92
1
4
Order By: Relevance
“…27 A recent angiographic study has indicated that antioxidant supplementation to lipid-lowering therapy prevented HDL-C elevation and was associated with a worse coronary angiographic outcome; 28,29 conversely, a predominant increase of HDL-C by gemfibrozil without a major reduction in LDL-C levels was associated with a significant reduction in the rate of coronary events. 30 Finally, patients with low HDL-C benefitted most when treated with fluvastatin in the Lipoprotein and Coronary Atherosclerosis Study (LCAS).…”
Section: Discussionmentioning
confidence: 99%
“…27 A recent angiographic study has indicated that antioxidant supplementation to lipid-lowering therapy prevented HDL-C elevation and was associated with a worse coronary angiographic outcome; 28,29 conversely, a predominant increase of HDL-C by gemfibrozil without a major reduction in LDL-C levels was associated with a significant reduction in the rate of coronary events. 30 Finally, patients with low HDL-C benefitted most when treated with fluvastatin in the Lipoprotein and Coronary Atherosclerosis Study (LCAS).…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, however, two studies were published which questioned the benefit of the combined therapies. Patients treated with simvastatin, niacin and a combination of different antioxidants (400 IU bis in die (BID; twice a day) vitamin E, 500 mg BID vitamin C, 12.5 mg BID β-carotene and 50 mg BID selenium) profited less than the simvastatin and niacin groups as the protective increase in HDL2 with simvastatin plus niacin was attenuated by concurrent therapy with antioxidants [243,244] . Tousoulis et al [245] treated patients suffering from ischemic heart failure with low dose atorvastatin (10 mg/d) alone or in combination with 400 IU/d vitamin E and found that vitamin E impairs the positive effects of atorvastatin, on, for example, endothelial function or inflammatory response.…”
Section: Interactions With Pharmaceuticsmentioning
confidence: 99%
“…The apo A-I promoter is sensitive to the oxidative state (61), and some antioxidants at high concentrations can suppress apo A-I promoter activity in Hep G2 cells (62). Clinical trials have also found that antioxidants may partially blunt HDL induction by simvastatin-niacin combination therapy (63). The precise role of micronutrient status in the diabetes-related reduction of apo A-I expression is not known.…”
Section: Effects Of Micronutrients On Apo A-i Expressionmentioning
confidence: 99%